Cultural Content Analysis of English Textbook “Bahasa Inggris 2” for Senior High School Grade XI - Agnes Dwi Iranta Purba; Siti Nurul Azkiya; Asri Nurul Qadri; Zaharil An’asy (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2023)
AbstractThis research aims to discover what and how culture is represented in the